ربا کے اسلامی متبادل: ایک تجزیاتی مطالعہ: An Analytical Study of Islamic Alternatives to Riba - Hassan Ur Rehman Taqvi; Dr. Muhammad Zubair Sheikh; Muhammad Khan (International Research Journal of Arabic and Islamic Studies, 2024)
Usury or Interest is strictly prohibited in Islam, and therefore Islamic banks have to find alternative ways to finance their operations and to gain profit. This paper explores the various Islamic alternatives to usury or interest, including profit-sharing, leasing, and mudarabah. It also discusses the challenges of implementing these alternatives and the huge potential benefits hidden in an Islamic banking system. Transitioning from a conventional interest-based system is complex, but necessary for a more just, equitable, and sustainable economy on a national level as well as on a global scale. This study lays the groundwork for further exploration of Islamic banking's role in achieving these goals.